Agriculture Output Growth in East Java: An Input-Output Analysis Beetwen 1985-1990 and 1994-2000 - Anindita, Ratya; Shinta, Agustina (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 10, No. 1 Februari 2010, 2010)
-